Pengaruh Disiplin dan Lingkungan Kerja Terhadap Kinerja Melalui Motivasi di PT. Varta Microbattery Batam - Hazriyanto, Dwi Astuti,; Prasetyo, Ary (STIE AMKOP, 2025)
This study aims to determine the effect of work discipline and work environment on employee performance through work motivation. The method used in this study is quantitative using a questionnaire as a research instrument. The data collection technique in this study is using a simple random sampling technique with a sample size of 85 people from a total population of 500 people. The analysis used in this study is the structural equality model (SEM) with Amos software version 24. The results of this study include work discipline has a positive value but is not significant to work motivation. The work environment has a positive and significant effect on work motivation. Work discipline has a negative value and is not significant to employee performance. The work environment has a negative value and is not significant to employee performance and work motivation has a positive and significant effect on employee performance.